Direct Observation of the Current Distributions across SOFC by Measuring the Lateral Voltage Differences. (2nd June 2015) - Devaraj, Abhilasha Sumangal; Yashiro, Keiji; Hashimoto, Shin-ichi; Kawada, Tatsuya
Abstract : In order to evaluate the current distribution across the SOFC, 32 probes were attached to the current collector on the cathode side to measure the lateral voltage difference at operating condition. To get the current distribution from lateral voltage differences, a charge conservation equation was used for calculation. In addition to the experiment, a simulation was also simultaneously done to compare the differences and the validity of the experimental procedures. The experimentally determined current distribution showed a big spike at near the current lead-in wires. With the simulation results, similar results were shown, which indicated this spike was an artifact in the calculation of the local current using a limited number of potential probes. Apart from this spike, this work shows the validation of the experimental results from the simulation and confirm that current distribution of SOFC can be calculated using charge conservation equation.